(untitled) (Research, Society and Development, 2023)
Erupted odontomas are rarely found in the oral cavity. To the best of our knowledge there are only a few cases reported of compound erupted odontoma. Also, different pathological conditions have been related to odontoma’s aetiology. This article describes a case report with review of a 17-year-old girl in investigation of Dravet syndrome, psychogenic nonepileptic seizures and psychotic disorder in whom it was identified an enamel-like tissue exposed in gingiva. The size of the lesion was around 2 mm and it was located between the right permanent mandibular lateral incisor and canine teeth. Periapical radiography revealed a radiopaque image of irregular tooth-like structures, suggesting the presence of an erupted compound odontoma. The lesion was surgically removed under infiltrative anesthesia and without the need for a flap. Four small tooth-like structures were removed, and the specimens were sent for histopathological analysis, confirming the hypothesis of compound odontoma. The procedure went without complications nor need of patient sedation. Twenty days after the surgery, there was satisfactory healing of the operated region’s tissue. Odontoma’s aetiology is not very well established yet, so it is unknown whether eventual epileptic seizures that occur during the period of dental formation and thus increase patient risk for accidental dental injuries could favor the development of these lesions.